(untitled) (Journal of Laboratory Animal Science, 2019)
A well-defined health status classification system helps veterinarians and researchers collaborate on planning experiments and aid them in defining facility procedures such as animal receipt and housing. This article will describe a rodent health classification system that has been used by Bristol-Myers Squibb in the U.S. and India to manage and maintain disease-free rodent colonies for research.